2020
DOI: 10.1007/s10067-020-05004-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sjögren’s syndrome associated with rheumatoid arthritis in the USA: an observational study from the Corrona registry

Abstract: The objectives of this analysis were to assess the prevalence of Sjögren's syndrome (SS) associated with rheumatoid arthritis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 19 publications
2
40
0
1
Order By: Relevance
“…From a temporality point of view, in a prospective study by Harrold et al, SS was diagnosed in 31.2% of patients with a primary RA diagnosis. This patient cohort manifested higher comorbidity rates, mainly infection [ 54 ]. In a study on patients with both RA and SS by Yang et al, the authors revealed that RA manifestations preceded in 64.8% of the patients, in 25.7% the two syndromes had synchronous inception, and only 9.5% of patients with SS developed RA in later stages [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a temporality point of view, in a prospective study by Harrold et al, SS was diagnosed in 31.2% of patients with a primary RA diagnosis. This patient cohort manifested higher comorbidity rates, mainly infection [ 54 ]. In a study on patients with both RA and SS by Yang et al, the authors revealed that RA manifestations preceded in 64.8% of the patients, in 25.7% the two syndromes had synchronous inception, and only 9.5% of patients with SS developed RA in later stages [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was noted clearly that patients with high disease activity and longer duration of disease, seropositivity, and females have higher incidence of sicca symptoms. 25,26 Peripheral neuropathy mostly presenting as mononeuritis multiples or mono or poly neuropathy and central nervous system presenting as stroke has significant impact on quality of life in rheumatoid arthritis patients. Our data showed 2.2% of patients complicated with neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The similarities between the aetiology and manifestation of fatigue in RA and SLE become less clear when considering multi-organ involvement. Sjögren's syndrome is prevalent in both conditions, affecting 15-30% of both patient groups, and has been associated with fatigue in multiple studies, independent of disease activity or pain conditions such as fibromyalgia [42][43][44][45].…”
Section: Mechanisms Of Fatigue and Association With Other Symptomsmentioning
confidence: 99%